THE ROLE OF PERSO-NALITIES ACTING AS HEADS OF PUBLISHING HOUSES ON MODERN BOOK PUBLISHING IN LITHUANIA - ANDRIUKAITYTĖ, RŪTA (Knygotyra, 2013)
The aim of the article is to investigate the impact of a personality heading a publishing house or a publishing business. The article has shown that almost all Lithuanian publishers are for-profit, small and micro-enterprises, where most of the different processes include a small number of people and the head of a publishing house comes into direct contact with all the publishing processes. The smaller the publishing house is, the more important the role of the head of a publishing house and his/her personality becomes. The analysis of a publisher’s personality was conducted on the basis of the adapted Big Five model, with the conclusion that a publisher’s personality is comparable to the personality characteristics of any entrepreneur. The personality-related analysis of Lithuanian publishers revealed that those Lithuanian publishers who founded a publishing house are often high-brow, artistic, romantic, ideological personalities who regard publishing more as a cultural mission than a commercial business. The empirical study (interviews conducted with several heads of Lithuanian publishing houses) has disclosed that the role of the head of a publishing house is also affected by such factors as literature genres and scope of publishing activities. It has been found out that the most important and influential personality in a publishing house is usually related to a thorough knowledge of the literature the respective publishing house is specializing in. The personalities of the Lithuanian publishers are not distinctly different from those of foreign publishers: all of them can be characterized as comprehensive and well-rounded personalities, having the ability to find and exploit new opportunities, motivated by the pursuit of lifelong learning, interested in team- work, displaying patience and creativity. The study also identified the following personality traits (which are otherwise not mentioned in literature) – instincts, intuition, the ability to value a book, knowledge of the publishing repertoire and devotion to it as well as cultural choice motives for the publishing industry. In conclusion, the Lithuanian publishers as personalities exert an extremely significant influence on contemporary image-making in Lithuania, which makes the situation in Lithuania different from the respective publishing landscape in foreign countries. Thus, the following conclusion can be drawn: a mere talent of a promising entrepreneur does not necessarily ensure a success in the publishing industry. To a large extent, success depends on a publisher’s comprehensive, well-educated and culturally sophisticated personality.